Consumer perception and behaviour retention in gyms and health clubs - Gonçalves, Celina (2011)
The present study aims to find out to what extent the perception that the members have from gyms and health clubs (GHC) contributes to the retention, through specific variables. It tries to go beyond the exclusive study of quality, searching for a set of dimensions and indicators of positioning as important factors for retention.